(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article deals with the issue of the integration of technology into language teaching and its role in improving speaking and listening skills in EFL classes. There were introduced the importance of technological tools and some practical implementations in using them for enhancing learners’ listening and speaking skill. The ideas were proved by the facts that student’s skills can be significantly increased by various technological tools such as blogs, quick pen, questionary as well as podcasting.